Effect of yoghurt processing on beta-casomorphin 5 and beta-casomorphin 7 concentrations using novel liquid chromatography-mass spectrometry methods - Nguyen, Duc Doan (Curtin University, 2015)
The effect of yoghurt processing on the concentration of beta-casomorphin 5 and beta-casomorphin 7 was investigated. Liquid chromatography-mass spectrometry methods were developed and validated. The milk beta-casomorphin 7 range was 0.13 and 2.38 ng/g and beta-casomorphin 5 was below limit of detection. Beta-casomorphin 7 was completely degraded when milk was fermented with individual bacteria or a mixture of L. delbrueckii ssp. bulgaricus and S. thermophilus at pH 4.5 and after 7 days of yoghurt storage.